Perfil dos estudos do departamento de ginecologia submetidos ao comitê de ética em pesquisa (CEP) da Unifesp no período de 2001 a 2012 com o objetivo de obtenção de títulos - Meleti, Andreia Reis Pereira [UNIFESP] (2016)
Objective: To determine the profile of the studies submitted to the Department of Gynecology at Unifesp, the institutional Ethics Committee from 2001 to 2012. Casuistry andMethods:This study was conducted in the Department of Gynecology, Universidade Federal de São Paulo. They were raised all research projects submitted to the Comitê de Ética em Pesquisaof UNIFESP between 2001 to 2012. Some specific characteristics were considered of each study as stratification by group according to specification resolution 466 of Conselho Nacional de Saúde(CNS), group characteristics, such as whether the study is a protocol of prospective or retrospective research, funding agency and academic goal. The data were tabulated in Excel table and presented in graphs. We analyzed all studies submitted in the period, a total of 590 studies already determined.Results:The results were presented through tables and graphs, and discussed at the end of the study.Conclusions:The knowledge of the profile and the ethical implications indicated by the Ethics Committee in these studies may contribute to future research projects,so that they may be designed more appropriately by their researchers.